Multidrug resistance of the extended-spectrum beta-lactamase-producing Klebsiella pneumoniae isolated in Tizi-Ouzou (Algeria) - Bariz, Karim; De Mendonça, Ricardo; Denis, Olivier; Nonhoff, Claire; Azzam, Amina; Houali, Karim (Cellular and Molecular Biology, 2019)
The emergence and spread of multidrug-resistant bacteria is a major public health concern. This study sought to investigate the phenotypic and genotypic characteristics of clinical isolates of ESBL-producing Klebsiella pneumoniae, at University Hospital of Tizi-Ouzou. Antibiotic susceptibility testing of the strains was carried out by the disc diffusion method, the ESBL production was screening by the Double Disc Synergy Test and confirmed by the Phenotypic Confirmatory Disc Diffusion Test. Genomic DNA was extracted using the Qiagen DNeasy Blood & Tissue Kit mini kit (Qiagen) according to the manufacturer's instructions.PCR targeting the genes blaCTX-M, blaTEM, blaSHV, blaVEB, blaGES, blaPER, blaBEL, blaVIM, blaIMP, blaKPC, blaNDM and blaOXA48 was performed. A CTX-M PCR-based grouping method was carried out using primers specific to the groups 1, 2 and 9. Conjugative transfer of plasmids was carried out using sodium azide-resistant recipient strain Escherichia coli K12. The phylogenetic relationship was determined by ERIC-PCR. All strains of K. pneumoniae tested shared ESBL producer's genes belonging to the CTX-M group 1. These strains showed a high level of resistance to íŸ-lactams, aminoglycosides, fluoroquinolones and trimethoprim/ sulfamethoxazole. Resistance to fosfomycin was also detected in one strain of K. pneumoniae. Only one carbapenem-resistant strain was isolated. Phylogenetic analysis showed 49 different genetic profiles of K. pneumoniae strains, showing the absence of clonality. This study revealed a high prevalence of ESBL belonging to the CTX-M group 1 in K. pneumoniae tested. The emergence of resistance to carbapenem and fosfomycin, could seriously limits the therapeutic choices options.